Metode Tafsir bil Ma’tsur dan Urgensinya Dalam Menjaga Otoritas Penafsiran Al-Quran - Lia Yuliasih; Ali Khosim; M. Athoillah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Tafsir bil ma’tsur is one of the Qur’anic exegesis methods that emphasizes transmitted reports derived from the Qur’an itself, the Sunnah of the Prophet Muhammad (peace be upon him), the statements of the Companions, and the interpretations of the Successors (tabi‘in). This method is regarded as the most authoritative form of interpretation due to its close connection to the original sources of revelation and the early generations of Islam. This article aims to examine the concept of tafsir bil ma’tsur, its sources, characteristics, as well as its strengths and limitations within the tradition of Qur’anic exegesis. This study employs a qualitative approach through library research by analyzing classical and contemporary scholarly works on Ulumul Qur’an and tafsir. The findings indicate that tafsir bil ma’tsur plays a crucial role in preserving the authenticity of Qur’anic interpretation through a verified transmission system. Nevertheless, this method also encounters challenges, including the mixture of authentic and weak narrations and the infiltration of Isra’iliyyat. Therefore, a critical and rigorous verification process is essential to ensure that tafsir bil ma’tsur remains methodologically sound and academically reliable.